Imaging robust microglial activation after lipopolysaccharide administration in humans with PET - Sandiego, Christine M.; Gallezot, Jean-Dominique; Pittman, Brian; Nabulsi, Nabeel; Lim, Keunpoong; Lin, Shu-Fei; Matuskey, David; Lee, Jae-Yun; O’Connor, Kevin C.; Huang, Yiyun; Carson, Richard E.; Hannestad, Jonas; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
Neuroinflammation is associated with a broad spectrum of neurodegenerative and psychiatric diseases. The core process in neuroinflammation is activation of microglia, the innate immune cells of the brain. We measured the neuroinflammatory response produced by a systemic administration of theEscherichia colilipopolysaccharide (LPS; also called endotoxin) in humans with the positron emission tomography (PET) radiotracer [11C]PBR28, which binds to translocator protein, a molecular marker that is up-regulated by microglial activation. In addition, inflammatory cytokines in serum and sickness behavior profiles were measured before and after LPS administration to relate brain microglial activation with systemic inflammation and behavior. Eight healthy male subjects each had two 120-min [11C]PBR28 PET scans in 1 d, before and after an LPS challenge. LPS (1.0 ng/kg, i.v.) was administered 180 min before the second [11C]PBR28 scan. LPS administration significantly increased [11C]PBR28 binding 30–60%, demonstrating microglial activation throughout the brain. This increase was accompanied by an increase in blood levels of inflammatory cytokines, vital sign changes, and sickness symptoms, well-established consequences of LPS administration. To our knowledge, this is the first demonstration in humans that a systemic LPS challenge induces robust increases in microglial activation in the brain. This imaging paradigm to measure brain microglial activation with [11C]PBR28 PET provides an approach to test new medications in humans for their putative antiinflammatory effects.